Identification of a central regulator of ginkgolide biosynthesis in Ginkgo biloba that integrates jasmonate and light signaling - Jinfa Du; Zhen Zhao; Lingqi Jin; Lijin Huang; Dian Jin; Xiaoyan Zheng; Qiaolei Wang; Wenbo Xu; Huijun Guo; Xinyue Xing; Raphael N. Alolga; Lam-Son Phan Tran; et al. (Proceedings of the National Academy of Sciences, 2025)
Ginkgolides are secondary metabolites unique to Ginkgo biloba with the potential to prevent and treat cardiovascular and cerebrovascular diseases. Although the biosynthetic pathways of ginkgolides have been partly uncovered, the mechanism regulating their biosynthesis is still largely unknown. Here, using multiomic and genetic analyses, we report the identification of a transcription factor, named ETHYLENE RESPONSE FACTOR ASSOCIATED WITH GINKGOLIDE BIOSYNTHESIS (GbEAG), as a critical regulator of ginkgolide biosynthesis. GbEAG is highly expressed in the roots of G. biloba, and its expression is significantly induced by methyl jasmonate (MeJA). Ginkgolide content was significantly increased in roots by overexpressing GbEAG using a “cut-dip-regeneration” system. GbEAG positively regulates ginkgolide biosynthesis by directly binding to the GCC-boxes in the promoter regions of genes involved in the biosynthesis of ginkgolides, such as ISOPENTENYL DIPHOSPHATE ISOMERASE ( GbIDI ) and CYTOCHROME P450 7005C3 ( GbCYP7005C3 ). GbEAG mediates the jasmonic acid (JA)-activated ginkgolide synthesis through its direct interaction with the JASMONATE ZINC-FINGER INFLORESCENCE MERISTEM DOMAIN 3 (GbJAZ3) repressor. Importantly, we also found that the central light-response regulator ELONGATED HYPOCOTYL 5 (GbHY5) mediates light induction of ginkgolide biosynthesis by binding to the G-box in the GbEAG promoter. Our findings provide mechanistic insights into the coordinated regulation of ginkgolide biosynthesis via JA and light signals, with GbEAG as a central regulator in G. biloba, and shed light on the potential to develop ginkgolide-rich varieties through molecular breeding and gene editing.